Synergic Extraction of Titanium (IV) with the New Solvent Tri-iso-amyl Phosphate (TAP) and Thenoyltrifluoroacetone (TTA) - Hasan, S. H.; Joshi, V. C.; Rupainwar, D. C. (1992)
The extraction of Ti (IV) from aqueous hydrochloric acid solution was investigated by using three different solvent systems: thenayltrifluoroacetone (TTA), a new solvent tn-iso-amyl phosphate (TAP)and a mixture of TTA and TAP, all diluted with carbon tetrachloride. An optimum of 90.34% and 97.45 % Ti(IV) was extracted when 4.0 % TTA or 33 % TAP was used, respectively. However, a significant synergic effect was observed even when half the concentration of the two extractants was used, i.e. a mixture of only 2.0% TTA and 16.0% TAP solution extracted as much as 99.03% of the metal from the aqueous HCl solutions. For all these three extraction systems concentrations of Ti(IV) and HCl were maintained at 1. 0 x 10J mol [1 and 11.5 mol [1, respectively. It was concluded that Ti(IV) forms a disolvate with both the ligands, i.e. TTA and TAP, but a 1:1 mixed solvate is formed when a TTA-TAP mixed ligand system is used. It was also established that the TTA combines in its undissociated form with the central metallic ion Ti(IV). The mathematical treatment ofthe three extraction systems showed that the average values of log Kafor the three systems were 2.48 (TTA), 1.60 (TAP) and 3.19 (TTATAP synergic system). It was also shown that the experimental value for the mixed solvate system is 7.06 times higher than the statistically evaluated value for the same system.